(untitled) (Confluenţe Bibliologice, 2018)
The year 2018 was declared the “Year of Stephen the Great and Saint, the ruler of Moldova”. In this context, in the Scientific Library USARB, several traditional and online exhibitions dedicated to the Grand Master were exposed.